Effect of Special Massage on Hamilton Anxiety Rating Scale (HARS) Scores among Primigravida Pregnant Women in the Third Trimester in Coping with Childbirth During the Covid-19 Pandemic - Raden Roro Ratuningrum Anggorodiputro; Tuti Wahmurty Sapi'i; Ahmad Faried (EMBRIO: Jurnal Kebidanan, 2023)
The spread of coronavirus during the Covid-19 pandemic has resulted in an increased level of anxiety among pregnant women. Decrease in the level of anxiety in pregnant women can be achieved through non-pharmacological therapy, one of which is special massage. This study aims to analyze the difference in the effect of special massage on the anxiety level between primigravida pregnant women in the third-trimester and pregnant women without special massage in coping with childbirth during the Covid-19 pandemic. This was a quasi-experimental study with a Non-equivalent Control Group Design approach. The samples in this study were 80 pregnant women in the third-trimester. The sample size was determined using the formula for unpaired categorical analytical study to test the hypothesis between the two proportions. The test results showed a comparison of anxiety scores (pre and post) in the two study groups, with a decrease in the HARS score in the special massage group by 43.7percent. Meanwhile, the decrease in the HARS score in the group without special massage was -9.1percent. The statistical test results with the Mann-Whitney test obtained a p-value less than equals 0.001 (p less than 0.05) which indicated a significant difference. It can be concluded that special massage had a significant effect on a decrease in the HARS Score of primigravida pregnant women in the third-trimester pregnant women in coping with childbirth during the Covid-19 pandemic.